Pelaksanaan Kebijakan Diskriminasi Positif Bagi Penyandang Disabilitas Untuk Memperoleh Pekerjaan di Kota Jambi - Nazifah, Nazifah; Somad, Kemas Abdul; Rostarum, Triamy (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
The aim of this research is to determine the implementation of positive discrimination policies for people with disabilities to obtain jobs in Jambi City. Empirical juridical research using a socio legal research approach. Data sources were obtained from field data and library data, data collection techniques used interviews and documentation, data were analyzed descriptively analytically. The research results show that the right of people with disabilities to get work is a constitutional right guaranteed in the 1945 Republic of Indonesia Constitution and various laws and regulations related to people with disabilities, employment and human rights. Positive discrimination policies are needed as an effort to protect and fulfill the rights of people with disabilities to get jobs in Jambi City in the form of ease of information and building accessibility as well as a quota system to fulfill the rights to get jobs for people with disabilities. The implementation of positive discrimination policies for people with disabilities in obtaining jobs in Jambi City in the future requires a form of positive discrimination policy that is based on the principle of justice and the application of the whole government concept as a form of data integration as an effort to empower people with disabilities, so that protection, fulfillment of rights, guidance and empowerment of people with disabilities disabilities to obtain work in Jambi City can be fulfilled